Exploring postoperative atrial fibrillation after non-cardiac surgery: mechanisms, risk factors, and prevention strategies - Jiang, Shengjie; Liao, Xiaozu; Chen, Yong; Li, Binfei (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation (AF) stands as the most prevalent persistent arrhythmia and a common complication after surgical procedures. Although the majority of non-cardiac surgery patients experience postoperative AF (POAF) and the condition is typically self-limited and asymptomatic, its detrimental impact on patient outcomes, prolonged hospitalization, and heightened risk of stroke and overall mortality has become increasingly evident. Of significant concern, POAF emerges as a noteworthy risk factor for stroke, myocardial infarction, and mortality in comparison to patients with non-surgical atrial fibrillation. Multiple studies have corroborated the association between POAF and an elevated risk of stroke and mortality. The development of postoperative atrial fibrillation is multifactorial, with the inflammatory response being a primary contributor; additionally, factors such as hypovolemia, intraoperative hypotension, anemia, trauma, and pain can trigger POAF. Risk factors for POAF in non-cardiac surgery primarily relate to age, hypertension, obesity, prior cardiac disease, obstructive sleep apnea, and male sex. Prophylactic treatment with β-blockers, amiodarone, or magnesium has demonstrated efficacy, but further trials are warranted, especially in high-risk populations. This review provides an account of the incidence rate, pathophysiology, and prognosis of atrial fibrillation after non-cardiac surgery, elucidates the underlying mechanisms of its occurrence, and explores various preventive strategies investigated in this domain.